Discriminating the Presence of Psychological Distress in Patients Suffering from Psoriasis: An Application of the Clinimetric Approach in Dermatology - Offidani, E; Del Basso, D; Prignago, F; Tomba, E (Acta dermato-venereologica, 2016)
Psoriasis is a chronic dermatologic disease that negatively impacts physical and mental health of patients as well as their social and work life. The aim of this study is to illustrate, by a clinimetric approach the differences in psychological distress and well-being between patients with mild and moderate to severe psoriasis. Seventy patients with psoriasis were evaluated using the Structured Clinical Interview for DSM-IV (SCID-I), the Diagnostic Criteria for Psychosomatic Research (DCPR), along with the following self-report instruments: the Symptoms Questionnaire (SQ), the Psychological Well-being scales (PWB) and the Temperament and Character Inventory (TCI). Illness severity was evaluated using the Psoriasis Area and Severity Index (PASI). While no differences were reported between groups in terms of psychiatric diagnoses, patients with greater severity (PASI <10) presented higher rates of demoralization (61.5%) and Type A behavior (53.8%) than subjects with mild severity (17.5% and 21.1%, respectively). Patients with moderate/severe psoriasis also reported impaired levels of psychological well-being in terms of lower autonomy, environmental mastery, personal growth and purpose in life. Furthermore, according to TCI, patients with severe psoriasis reported greater harm avoidance and lower self-directness than individuals with milder psoriasis levels. Overall results highlighted the need in psoriasis care of a more comprehensive psychological and psychosomatic assessment not limited to the customary psychiatric diagnostic criteria.